Defensive system of ancient city Volubilis. State of research and new perspectives - Czapski , Maciej (Studia Europaea Gnesnensia, 2017)
This contribution presents the first results of two surveys (2014, 2016) in the vicinity of the ancient city of Volubilis, situated in the southern part of the Roman province Mauretania Tingitana. The main purpose was to assess the possibilities of non-invasive research of the forts established by the Romans as part of the defensive system of Volubilis and to investigate the character of the Roman defences on the southern border. Forts were connected with watchtowers which completed the system protecting the territory in question. Many interesting fragments of pottery have been found at those sites, which may confirm Roman presence in many, though not all points. Collected field information as well as the analysis of publications leads to the conclusion that the border defence arrangements at Volubilis might not be considered as a part of a centrally organised limes system, safe guarding the entire province, but as the defensive system of the city and its surroundings.